Geographical analysis of Rural settlements in Gwer sub district and it’s impact on Agricultural Development A Geographical Study - Tanka Othman Saeed (Zanco Journal of Humanity Sciences)
The Rural settlements are one of the population settlement types which became a center of human stability undoubtedly there are many factors impacted on the image of rural settlement distribution which they might be physical or human factors the rural population or countryside’s interest which agriculture in the sites which are suitable for this sector. Thus the agriculture profession has it’s important role for getting the rural citizens to agricultural development stage in the time of implementation of all the necessary conditions.The importance of this study is the strategic location of study area as well as it regards as an agricultural area due to it’s fertile soil. However there no any required academic study about this site.